BS EN 17670-2. Plastics piping systems for non-pressure underground conveyance and storage of non-potable water. Manholes, inspection chambers and road gullies for storm water systems made of unplasticized polyvinyl chloride (PVC-U), polypropylene (PP) and polyethylene (PE). Part 2. Specification for road gullies (20th May 2021) - British Standards Institution,
No abstract available